A Reversible Spectrophotometric Method Based on a Coupled Microfluidic Chip for Highly Selective Ammonium Detection - Hao Zhou (Journal of Chemistry, 2019)
A coupled chip aiming at economical and highly selective ammonium detection was fabricated. It consisted of a reaction chip, a gas-diffusion chip, and a detection chip. Zinc tetraphenylporphyrin dyed on the cation-exchange resin microbeads was used as the indicating material to avoid excess consumption for its reversibility. PDMS was selected as the material of the gas-diffusion membrane. A portable spectrometer was applied for spectrum analysis. By analysis of spectrum change, the high selectivity was confirmed because no component had interference on detection effect. Good performance was shown for all the tested concentrations (0.2–50 mg·L−1). The stability and reversibility were also judged by the spectrum data obtained from the indicating process and the recovering process. Finally, real samples containing ammonium were tested and the results were compared to those came from a standard method to confirm the accuracy of our method.